STUDENTS’ FEEDBACK OF PEER TEACHING TECHNIQUE ENGAGED IN ENGLISH LANGUAGE TEACHING OF ENGLISH DEPARTMENT - Sakinah, Yanik Lailinas; Agustina, Hiqma Nur (Journal of Innovation Research and Knowledge, 2024)
In the education field, feedback is necessary to be conducted to improve the performance either positive and negative feedbacks. This study aimed to elaborate the students’ feedback on peer teaching technique applied in English language teaching subject. The descriptive qualitative was used to scrutinized the data from observation, questionnaire and interview from 28 students. The results showed that there were three positive feedbacks during performance. The satisfaction, improvement and effectiveness. While the negative feedbacks were on the preparation and management time of applying peer teaching technique. These results would assist the lecturer to have a better performance in the next activities.